It’s All in the Name: Redressive Translation, Passive/Active Redressive Translation - Cox, Amanda (TTR, 2019)
Resistance in translation is a well known and accepted means for minorities and oppressed linguistic/cultural groups to access power, agency, and cultural repair (see Niranjana, 1992; Simon, 2005; Bandia, 2008; Cox, 2009; Tymoczko, 2010). Yet for all the good “retranslations” do, they remain yoked to a name that erases their significance by collapsing it with the simple act of “translating-again.” This paper argues for the adoption of a new term, “redressive translation,” to replace the term “retranslation” in contexts where redressive resistance in translation is manifest. It examines and defines two distinct varieties of redressive translation, namely “active redressive translation” and “passive redressive translation.” By adopting the name “redressive translation” to identify characteristics present in translated texts that resist politically and offer minority/minoritized cultures a means of healing, new clarity and strength can be brought to these translation offerings, enabling readers, researchers, translators, writers, and activists alike to share a common term for these essential articulations/manifestations of resistance.